Manajemen Kinerja di Otoritas Anti Korupsi : Studi Kasus Indonesia dan Swedia - Sativa, Oryza; Daskalakis, Christos (Komisi Pemberantasan Korupsi, 2018)
This paper investigates how Anti-Corruption Authorities (ACA) make use of performance measurement in order to improve performance management. The research framework has been developed from Ferreira and Otley (2009). The authors used a qualitative method with multiple case study in order to perform comparative research. Indonesia’s Komisi Pemberantasan Korupsi and Swedish National Anti-Corruption Unit were chosen as the sample of the study. The research found that both of the authorities has a greatly different performance management system and performance measurement. It can be seen from the use of key performance indicators and its role in the management control system, as well as the target setting, performance evaluation, and rewards.